KERAGAMAN JENIS TUMBUHAN PAKU (PTERIDOPHYTA) DI TEPIAN SUNGAI KEMBANG DESA ARANIO KABUPATEN BANJAR - Faizza, Kamila Nur; Ajizah, Aulia; Rezeki, Amalia (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Pteridophyta is one of the plants that has many benefits, both in terms of ecology, economy, and pharmacology. However, Pteridophyta still gets less attention when compared to other types of plants. Therefore, it is necessary to carry out an inventory study of the Pteridophyta species on the banks of Kembang River, Aranio Village, Banjar Regency. This study aims to describe the types of ferns (Pteridophyta) on the banks of Kembang River, Aranio Village, Banjar Regency. The sampling method used is the total exploration method by walking along the right and left banks of the river that can be passed on foot. In addition, environmental parameters were also measured, including light intensity, wind speed, soil pH, soil temperature, soil moisture, air humidity, altitude, and air temperature. Based on the results of the study, the ferns found were 6 families with 12 species, both terrestrial and epiphytic. The types of ferns found are Pteris vittata, Pteris ensiformis, Pityrogramma calomelanos, Adiantum lunulatum, Dryopteris marginalis, Pleocnemia conjugata, Christella dentata, Lygodium circinatum, Selaginella willdenowii, Tectaria polymorpha, Pyrrosia piloselloides, and Drynaria quercifolia.